Interdental Papilla Length and the Perception of Aesthetics in Asymmetric Situations - Yung Cheng Paul Yu; Ahmed Alamri; Helena Francisco; Sang-Choon Cho; Stuart Hirsch (Hindawi Limited, 2015)
The purpose of the study was to determine if there was a difference in the perception of aesthetics, by dental specialty, using computer assisted asymmetric alteration of the papilla length in the aesthetic zone with an apical alteration of the contact point of the clinical crowns. Standardized photographs were presented to sixty-five randomly selected dentists from New York University College of Dentistry on a computer screen for evaluation. Then, the dental professionals were asked to rate the smile in each picture. Control and experiment photographs were used. Data was analyzed using the statistical package SPSS version 21 and one-way ANOVA. The perception of esthetics depends on the dental professional specialty; results provide evidence that asymmetric deficiency in papilla length of 2 mm or more is perceived as "unattractive" by the dental specialists.